2015
DOI: 10.1177/0891243215599647
|View full text |Cite
|
Sign up to set email alerts
|

“I Am Not Just a Feminist Eight Hours a Day”

Abstract: This article focuses on youth feminist political action in Ecuador and Peru and its relationship to contemporary gender hierarchies. I examine how and why youth gender justice activists understand their political action differently from the professionalized adult feminists who mobilize them. Grounded theory was used to collect and analyze interviews with 21 young women and men activists on gender justice. Youth activists seek cultural changes using social advocacy to target the family, household, and intimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The qualitative methodology (focus groups and semi-structured interviews with an innovative guide) used in this study provided information that can serve as a guide to how to direct GBV prevention efforts. Moreover, just as the voices of activists have been shown to be key in other studies (Coe, 2015;Goicolea et al, 2014), they have helped us to better understand how GBV intersects with social constructs around gender because of their previous reflexivity and experience on the subject. We found that the hegemonic construction of masculinity favors a context of social pressure that makes men feel insecure and distrustful when intervening in a situation of violence (Bolton et al, 2022), which is complemented by the social questioning and blame of women who are victims of violence (Taylor, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative methodology (focus groups and semi-structured interviews with an innovative guide) used in this study provided information that can serve as a guide to how to direct GBV prevention efforts. Moreover, just as the voices of activists have been shown to be key in other studies (Coe, 2015;Goicolea et al, 2014), they have helped us to better understand how GBV intersects with social constructs around gender because of their previous reflexivity and experience on the subject. We found that the hegemonic construction of masculinity favors a context of social pressure that makes men feel insecure and distrustful when intervening in a situation of violence (Bolton et al, 2022), which is complemented by the social questioning and blame of women who are victims of violence (Taylor, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to address in depth different discursive perspectives and situations on self-identified cisgender people. Furthermore, research carried out in other countries such as Ecuador and Peru (Coe, 2015; Goicolea et al, 2014) shows that discourses of young adults involved in feminist activism can be key in framing the problem and proposing alternatives to challenge hegemonic masculinities and GBV. Until now, their voices have not been particularly studied in Spain, so it is of interest to incorporate them as they may shed light on discourses that might be different from those of non-activists.…”
Section: Introductionmentioning
confidence: 99%
“…In theoretical coding, I analyzed the connections between categories and found that while some depicted how the young adult feminist activists understood and practiced feminist mobilizing, other categories clarified why they did so in this way. I first published my findings that showed how the young adult feminist activists pursued a strategy of politicizing the sociocultural in response to blurred gender inequalities as an emergent social condition (Coe 2015). Here, I present the findings that show how they mobilized as an emergent feminist movement in response to a well-developed feminist movement.…”
Section: Methodsmentioning
confidence: 95%
“…The making of agenda emerged at a time of increasingly visible youth activisms around the globe calling out and calling time on the new twists and turns of enduring gender and sexual violence (see Damodar, 2012;Atluri, 2013;Coe, 2015;Mitchell and Ezcurra, 2017;Shefer, Hearn, Ratele and Boonzaier, 2018;Terriquez, Brenes and Lopez, 2018;Ridwan and Wu, 2018;Mendes, Ringrose and Keller, 2019). Enabled by a macro-political statement in the Welsh government practitioner guide which specifically invites young people to get involved in local and global activisms as part of a whole-school approach to healthy relationships, AGENDA as order-word could be up front about its proto-political intentions from the get-go.…”
Section: Agenda: Becoming-politicalmentioning
confidence: 99%